Glycosylated RNAs: discovery and implications in cancer biology - Tang, Shuai; Wang, Ximo; Chen, Fangmin; Li, Benyi (Frontiers in Oncology, 2026)
Glycosylated RNAs (glycoRNAs) are a newly discovered class of biomolecules that challenge the long-standing paradigm that glycosylation occurs exclusively on proteins and lipids. Early studies indicate that glycoRNAs are broadly distributed across cell types and can be detected at the cell surface as well as in other cellular compartments. Emerging evidence suggests that glycoRNAs may participate in processes such as intercellular communication and immune regulation, but their context-dependent functions in physiology and disease, including cancer, are only beginning to be elucidated. Recent advances in detection techniques have enabled more comprehensive profiling of glycoRNAs and their associated cell-surface RNA-binding proteins, providing initial links between glycoRNA patterns, tumor aggressiveness, immune checkpoint regulation and extracellular vesicle–mediated signaling. However, many of these connections remain correlative or are inferred by analogy to protein and lipid glycosylation. In this review, we summarize current knowledge of glycoRNA biosynthesis, cell-surface display and detection methods, with a particular focus on emerging observations in cancer-related contexts. We also discuss the potential of glycoRNAs as biomarkers and therapeutic targets, while highlighting key unanswered questions regarding their biosynthetic pathways, structural diversity and mechanistic roles. Addressing these challenges with integrated omics and spatial approaches will be essential for defining glycoRNA biology and evaluating their feasibility as tools for precision oncology.